STANDARD CLAUSES IN FUND DEPOSIT AGREEMENTS IN PERSPECTIVE OF UNDANG UNDANG PERLINDUNGAN KONSUMEN - Harjono, Dhaniswara K (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The use of standard agreements or standard clauses in economic activities in offering goods or services produced by business actors is a necessity and demand. This is also the case in the operational activities of banks in carrying out their business activities as intermediaries for both depositor and debtor customers. In practice, the use and application of new agreements in the banking world is not without problems. Standard agreements that are applied to customers, especially depositor customers, contain many injustices for depositors that violate the principle of balance. Including violations of a number of provisions stipulated in Article 18 of the Consumer Protection Law, including the presence of an ecosenary clause or exclusion clause, writing or letters that are small so that it is difficult to read or understand their meaning.